REMOTE DIAGNOSTICS OF TURNOUTS STATE ON TIMING AND SPECTRAL COMPOSITION IN CURRENT CURVE - Buryak, S. Yu.; Gavrilyuk, V. I.; Hololobova, O. O.; Kovryhin, M. O. (Science and Transport Progress, 2015)
Purpose. Development and implementation the points system diagnostics that would allow determining remotely the current state of turnout with all possible faults, gradual and sudden failures, damages, and in real time to report about their appearance. Methodology. State diagnostics on the values analysis of turnout main parameters is proposed to carry out with the help of a computer and analog-to-digital converter (ADC). Connecting measurements performance is advisable to produce to a shunt ammeter, installed in the working circuit of the point feed panel. ADC converts the analog signal of lost volts at the shunt into digital form and transmits it to a computer which stores the received data on its own recording medium for their further processing and storage. There is special software that is capable to reconnect signal and construct its temporal characteristic as well as decompose it on the spectral components. Using it one can analyze the obtained data, which allows diagnosing state of points upon change the nature, values and composition of the current curve. Findings. The computer diagnosis method was confirmed in practice for possible indications of problems that are associated with both the mechanical part of the turnout and the electrical part of it, while controlling parameters such as the amount of current normal transition, when working on frictions, the duration of the transition, properly adjusted headset and attachment points, the state of the motor. Originality. The use of computer technology in the diagnosis of the state of turnouts during their operation to monitor the current values of technical indicators, analysis and storage for all types of electric switches with different types of engines both DC and AC occurs through digitization and recording signal from measuring shunt of point feeder panel. Practical value. The proposed method enables timely, still in the early stages of defect parts, damages or failures of nodes mechanisms to detect and eliminate them. In addition, it reduces the load on the electrical engineers during schedule maintenance. The introduction of a diagnostic analysis of the turnout using computer technology will allow defining the appearance of faults in the early stages of their formation and preventing development the difficult avoidable damages or necessity for their complete replacement.